(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Traffic congestion is the one of the reasons for accidents and delay for ambulance journey to save patients life. Due to that ambulances reach the hospital. To avoid this problem and providing solution for this we are designing a smart and easily transporting system. The proposed system implemented with RF transmitter module activation. When the RF receiver signal receives the data then second section receive the data through RF receiver and turn traffic signals to green. The proposed approach is fully automated controlling the traffic lights thereby helping to reach the hospital in time. By using RF technology, it can send the data to traffic system when the ambulance vehicle is art longer distance then traffic automatically turns to clear traffic for this vehicle. Then only the emergency vehicle is quickly served and can reach the destination in time.